Biometric Analysis on Lean Logistics: WOS Database (1994 –2022) - Handan Öztemiz (Journal of Transportation and Logistics)
Lean logistics optimizes costs, making it a critical supply chain management (SCM) strategy. Avoiding unnecessary costs has been one of the most essential objectives in SCM, making it a primary field of focus for practitioners and academics. After 1990, future researchers aimed to determine how SCM, which has gained importance as a multienterprise and multiactor management style, can handle lean logistics and identify gaps and opportunities in the literature. This study presents a comprehensive bibliometric analysis of academic articles published on lean logistics in 1994–2022. RStudio-Biblioshiny software was used to perform a cocitation analysis of 559 lean logistics documents retrieved from the Web of Science database, using “lean logistics” as a keyword. This research reveals the most influential lean logistics research publications/citations and their research contributions. The analysis examined the primary research themes in the field, knowledge groups, keywords, country and author productivity, author and country collaboration, and cocitation network analysis between articles and sources. The broad perspective of lean logistics is briefly summarized for future researchers.